Efficacy of an Immune Modulator in Experimental Chlamydia trachomatis Infection of the Female Genital Tract - Joseph M. Lyons; James I. Ito; Servaas A. Morré (Hindawi Limited, 2006)
Objective. The aim of this study was to determine if vaginal application of the immune response modifier imiquimod (Aldara cream, 3M Pharmaceuticals, St Paul, Minn) would alter the course and/or outcome of female genital tract infection with a human isolate of Chlamydia trachomatis in a murine model. Methods. Groups of CF-1 mice were treated with Aldara on three different schedules: (1) ongoing beginning 5 days prior to and continuing through day 5 of infection; (2) a single prophylactic dose 2 hours prior to infection; and (3) therapeutic from day 4 to day 14 of infection. Mice were infected vaginally with a serovar D strain of C trachomatis, and monitored by culture to determine the level of shedding and duration of infection. Results. We observed a significant reduction in both duration of infection and the level of shedding during the acute phase in mice treated on an ongoing basis commencing 5 days prior to infection. There was no effect with respect to the other regimens. Conclusion. These results demonstrate that ongoing Aldara treatment has efficacy and may enhance local innate immunity which reduces the duration of subsequent infection with human isolates of C trachomatis in a murine model of female genital tract infection.